1988
DOI: 10.1001/archderm.1988.01670070023012
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Skin Grafts

Abstract: ages. The use of autologous skin grafts has been the "gold standard" for wound closure, but in patients with wounds of large surface area, such as extensive burns, this strategy cannot be realized because of the lack of adequate donor sites for grafting. Because the ultimate outcome of many burn patients is determined by wound coverage, temporary coverage of wounds with materials other than the patient's own skin has been performed in these situations using fresh or cadaver skin allografts from related or unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It has also been reported that cultured sheet grafts eventually reform a dermal-like subepithelial region, but only after extended periods, as long as 4-5 years (Gallico and O'Connor, 1985;Tittlekow and Scott, 1986;Phillips, 1988). A characterization of this "neo-dermis" after the transplantation of keratinocyte autografts on the muscle fascia in burn patients has been reported (Woodley et al, 1990).…”
Section: Advantages Of Keratinocyte Sheet Grafting From a Clinical Pementioning
confidence: 95%
“…It has also been reported that cultured sheet grafts eventually reform a dermal-like subepithelial region, but only after extended periods, as long as 4-5 years (Gallico and O'Connor, 1985;Tittlekow and Scott, 1986;Phillips, 1988). A characterization of this "neo-dermis" after the transplantation of keratinocyte autografts on the muscle fascia in burn patients has been reported (Woodley et al, 1990).…”
Section: Advantages Of Keratinocyte Sheet Grafting From a Clinical Pementioning
confidence: 95%
“…Freshly cultured autologous and allogeneic keratinocytes are reported to be useful to treat wounds resulting from burns to leg ulcers. [11][12][13][14][15][16][17][18] Allogeneic cultured keratinocytes offer the advantages of availability and obviate the need for harvesting skin. They are reported to enhance wound healing, [19][20][21] offering a reduced mean time to complete closure.…”
Section: Keratinocyte Culturesmentioning
confidence: 99%
“…In contrast, separation by the more traditional enzyme, trypsin, causes dispersion of the cells (Green et al, 1979). This neutral protease (DII) has also been used to obtain confluent sheets of cultured human epidermal cells to use for autografting (Green et al, 1979;Phillips 1988). In our experiments, embryonic avian epidermis could be isolated as a continuous sheet with DII for either immediate examination or organ culture experiments.…”
Section: Discussionmentioning
confidence: 99%